A practical guide and perspectives on the use of experimental pain modalities with children and adolescents. (March 2014) - Birnie, Kathryn A; Caes, Line; Wilson, Anna C; Williams, Sara E; Chambers, Christine T
SUMMARY Use of experimental pain is vital for addressing research questions that would otherwise be impossible to examine in the real world. Experimental induction of pain in children is highly scrutinized given the potential for harm and lack of direct benefit to a vulnerable population. However, its use has critically advanced our understanding of the mechanisms, assessment and treatment of pain in both healthy and chronically ill children. This article introduces various experimental pain modalities, including the cold pressor task, the water load symptom provocation test, thermal pain, pressure pain and conditioned pain modulation, and discusses their application for use with children and adolescents. It addresses practical implementation and ethical issues, as well as the advantages and disadvantages offered by each task. The incredible potential for future research is discussed given the array of experimental pain modalities now available to pediatric researchers.